2009
DOI: 10.1149/1.3142391
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Particle Composite Plating with Ni–P Alloy Matrix

Abstract: Ni-P alloy films containing phosphorus particles ͑called "Ni-P alloy composite films"͒ were fabricated by electrodeposition and were subsequently subjected to heat-treatment. Their compositions and microstructures were characterized, and their friction properties were evaluated using a ball-on-plate method. Composite electroplating in the nickel sulfate and chloride bath containing phosphorus acid and micrometer-sized phosphorus particles resulted in the Ni-P alloy coating with enhanced deposit phosphorus cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…S7a, ESI†). These results were in good accordance with the previous literature on the electrodeposition of Ni x P. 45–47 For simplification, the thus-fabricated reference sample was temporarily denoted as a -Ni x P/NF.…”
Section: Resultssupporting
confidence: 90%
“…S7a, ESI†). These results were in good accordance with the previous literature on the electrodeposition of Ni x P. 45–47 For simplification, the thus-fabricated reference sample was temporarily denoted as a -Ni x P/NF.…”
Section: Resultssupporting
confidence: 90%
“…However, because the underlayer used in the present study was also Cu, it was difficult to distinguish the diffraction peak of the sheets from those of the underlayer. We therefore applied an amorphous Ni–P coating on a Cu substrate by electroplating using a bath (an aqueous solution consisted of 0.2 M C 6 H 5 Na 3 O 7 , 0.5 M (NH 4 ) 2 SO 4 , 0.1 M NiSO 4 ·6H 2 O, and 0.2 M NaH 2 PO 2 ·H 2 O) at a charge amount of 450 C cm –2 (equal to the film thickness of about 40 μm) . As shown in Figure b, obvious diffraction peaks derived from the Cu substrate were not detected, which enabled us to explore the crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore applied an amorphous Ni−P coating on a Cu substrate by electroplating using a bath (an aqueous solution consisted of 0. 39 As shown in Figure 2b, obvious diffraction peaks derived from the Cu substrate were not detected, which enabled us to explore the crystal orientation. When the Cu electroplating treatment by 3.8 C cm −2 was conducted, diffraction peaks located at 43.5°, 50.5°, and 74.2°were detected, and the peaks originated from Cu planes of (111), (100), and (110), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Little work has been carried out in literature. Suzuki et al [4] studied "the co-deposition of aluminium oxide particles from an aqueous AgSCN bath". "It was concluded that the aluminium oxide particles adsorbed on the electrode and repressed Ag deposition.…”
Section: Introductionmentioning
confidence: 99%